Lung Cancer in a Male Smoker Treated by Adjunct Nutritional and Phyto-Therapy - Yap, Steve (International Journal of Biotechnology for Wellness Industries, 2013)
Current understanding of the aetiology of lung cancer suggests that oxidative stress is strongly implicated in its pathogenesis with both internal cellular production of free radicals and external carcinogens such as from tobacco smoke. Other risk factors include family history, exposure to radiation, chronic obstructive pulmonary disease, overweight, chronic inflammation, and poor dietary habits. Patient's survival rates have not changed appreciably suggesting that Western conventional therapeutic advances have been rather slow. This case study shows how a well-designed nutritional and phyto-therapy may offer an effective adjunct treatment for non-small cell lung cancer (NSCLC). The protocol included dietary and lifestyle modifications as well as the use of evidence-based nutraceuticals and herbs. The terminal cancer patient in question was diagnosed by his oncologist as being cancer-free after five months or so. According to ANMP (www.anmp.org.my), such a protocol treats, controls, and/or prevents chronic metabolic disorders such as cancer by impacting on the patient's physiological, hormonal, and/or immune functions.